Aspects of Dance Teacher Education: Analysis of Students’ Dance Education Research - Banevičiūtė, Birutė (Pedagogika, 2015)
Learning paradigm orients teacher to be a consultant, assistant, researcher ready to apply evidence based teaching. To prove research competence future dance teachers have to perform a dance education research. This study revealed pedagogical problems which interest future dance teachers: attitudes and motivation, dance in schools, dance teacher education, dance for people with special needs. Choise of research methods shift from quantitative towards qualitative.